Mimicking the Human Tympanic Membrane: The Significance of Scaffold Geometry. Issue 11 (4th May 2021) - Anand, Shivesh; Stoppe, Thomas; Lucena, Mónica; Rademakers, Timo; Neudert, Marcus; Danti, Serena; Moroni, Lorenzo; Mota, Carlos
Abstract: The human tympanic membrane (TM) captures sound waves from the environment and transforms them into mechanical motion. The successful transmission of these acoustic vibrations is attributed to the unique architecture of the TM. However, a limited knowledge is available on the contribution of its discrete anatomical features, which is important for fabricating functional TM replacements. This work synergizes theoretical and experimental approaches toward understanding the significance of geometry in tissue‐engineered TM scaffolds. Three test designs along with a plain control are chosen to decouple some of the dominant structural elements, such as the radial and circumferential alignment of the collagen fibrils. In silico models suggest a geometrical dependency of their mechanical and acoustical responses, where the presence of radially aligned fibers is observed to have a more prominent effect compared to their circumferential counterparts. Following which, a hybrid fabrication strategy combining electrospinning and additive manufacturing has been optimized to manufacture biomimetic scaffolds within the dimensions of the native TM. The experimental characterizations conducted using macroindentation and laser Doppler vibrometry corroborate the computational findings. Finally, biological studies with human dermal fibroblasts and human mesenchymal stromal cells reveal a favorable influence of scaffold hierarchy on cellular alignment and subsequent collagen deposition. Abstract : Understanding the influence of geometry in tympanic membrane scaffolds is critical for engineering biomimetic tissue replacements. This work combines different theoretical and experimental approaches to investigate the contribution of independent anatomical features of the tympanic membrane. The resultant mechanical, acoustical, and biological responses of the chosen architectures highlight the role of their corresponding radial and circumferential arrangements.